Pengaruh Content Marketing dan Harga Terhadap Keputusan Pembelian pada Saji Resto & Cafe di Citayam - Rizqia Fitriani Hamidah; Elmira Siska (Indo Publishing, 2026)
This study aims to determine the influence of content marketing and price on purchase decisions at Saji Resto & Cafe in Citayam. The research employed a quantitative method with a quantitative approach. Data were collected through the distribution of online questionnaires using Google Forms to consumers who had made purchases at Saji Resto & Cafe. The sampling technique used was purposive sampling, with a total sample of 100 respondents determined using the Lemeshow formula. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 30, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) test. The results of the study indicate that content marketing has a positive and significant effect on purchase decisions partially, with a calculated t-value of 5.606 and a significance value of 0.000. Price also has a positive and significant effect on purchase decisions, with a calculated t-value of 3.406 and a significance value of 0.000. Simultaneously, content marketing and price have a positive and significant effect on purchase decisions, with a calculated F-value of 233.465 and a significance value of 0.000. These findings suggest that the better the content marketing and the more appropriate the price offered, the higher the consumers' purchase decisions at Saji Resto & Cafe in Citayam.